An exploratory study of the performance of normal Indian listeners on the staggered spondiac word test developed in English for Indian population - Chandrashekar SS (Journal of All India Institute of Speech and Hearing, 1970)
The Staggered Spondiac Word Test offers the diagnostician many sources of information concerning an individual's ability to respond to and.cope with complex speech stimuli. Higher auditory functioning from b.'.lth theoretical and diagnostic points of view is now receiving considerable interest